Size Controlling of ZnS Quantum Dots Synthesized by Ultrasonic-assisted Chemical Precipitation - Quynh, Luu Manh; My, Nguyen Thi Tra; Nhung, Bui Thi Hong; Nam, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics; Vol 32 No 1, 2016)
Abstract: ZnS quantum dots (QDs) are prepared by ultrasonic-assisted chemical precipitation method with the presence of different concentration Trisodium citrate (TSC). The TSC molecules play very important role in inhibiting the growth of the ZnS particles.  The mean size of the ZnS crystals which is estimated from the X-ray diffractions decreases from 1.7 nm to 1.4 nm when the added amount of the TSC increases. The lattice constant of the particles decreases from 5.40 Å to 5.38 Å and the band gap of the material increases from 3.92 eV to 4.74 eV. The particles are well dispersive in aqueous solution and emit blue light at around 430 nm while being excited by 320 nm ultraviolet light, which guarantees good attitude for further biological applications. Keywords: ZnS, size controlling, ultrasonic, precipitation